1990
DOI: 10.1007/bf02097366
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Toda systems

Abstract: Abstract. We present and study Poincare-invariant generalizations of the Galilei-invariant Toda systems. The classical nonperiodic systems are solved by means of an explicit action-angle transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
310
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(316 citation statements)
references
References 23 publications
3
310
0
3
Order By: Relevance
“…[29,67]). 5 Another interesting problem is the relation between the g quantization conditions obtained for the relativistic Toda lattice (and also, presumably, for the Goncharov-Kenyon integrable system) and the approach based on quantizing the mirror curve presented in [29], which involves a single quantization condition encoded in the vanishing of a (quantum) theta function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[29,67]). 5 Another interesting problem is the relation between the g quantization conditions obtained for the relativistic Toda lattice (and also, presumably, for the Goncharov-Kenyon integrable system) and the approach based on quantizing the mirror curve presented in [29], which involves a single quantization condition encoded in the vanishing of a (quantum) theta function.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding monodromy matrix is 5) and it can be shown that 2t(z; R) = Tr T(z; R) (2.6) satisfies the commutation relation…”
Section: The Relativistic Toda Latticementioning
confidence: 99%
See 1 more Smart Citation
“…Following [GK13], by a cluster integrable system we mean an integrable system whose phase space is a cluster variety equipped with its canonical Poisson structure. Examples include those studied in [GK13,FM14,HKKR00,Wil13a], and generally encompass those referred to as relativistic integrable systems in the literature [Rui90]. Roughly, cluster varieties are Poisson varieties whose coordinate rings (cluster algebras) are equipped with a canonical partial basis of functions called cluster variables [FZ02].…”
Section: Introductionmentioning
confidence: 99%
“…Among quantum integrable models, the τ 2 (BBS)-model [1] plays a special role for its unique properties, e.g., it is one of the simplest quantum integrable models associated with cyclic representation of the Weyl algebra; it allows to include multiple inhomogeneity parameters on each single site without breaking the integrability of the model; and more interestingly, the τ 2 -model under certain parameter constraint is highly related to some other integrable models such as the chiral Potts model [2][3][4][5][6][7] and the relativistic quantum Toda chain model [8]. Many papers have appeared in literature for such connections and many efforts have been made to obtain the solutions of chiral Potts model by solving the τ 2 -model with a recursive functional relation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%